Neurotransmitter release progressively desynchronizes in induced human neurons during synapse maturation and aging - Burak Uzay; Aiden Houcek; Z. Zack Ma; Christine Konradi; Lisa M. Monteggia; Ege T. Kavalali (Cell Reports, 2023)
Summary: Rapid release of neurotransmitters in synchrony with action potentials is considered a key hardwired property of synapses. Here, in glutamatergic synapses formed between induced human neurons, we show that action potential-dependent neurotransmitter release becomes progressively desynchronized as synapses mature and age. In this solely excitatory network, the emergence of NMDAR-mediated transmission elicits endoplasmic reticulum (ER) stress leading to downregulation of key presynaptic molecules, synaptotagmin-1 and cysteine string protein α, that synchronize neurotransmitter release. The emergence of asynchronous release with neuronal maturity and subsequent aging is maintained by the high-affinity Ca2+ sensor synaptotagmin-7 and suppressed by the introduction of GABAergic transmission into the network, inhibition of NMDARs, and ER stress. These results suggest that long-term disruption of excitation-inhibition balance affects the synchrony of excitatory neurotransmission in human synapses.